EFFECT OF THE CONSTRUCTIVIST INSTRUCTION APPROACH ON ACHIEVEMENT AND RETENTION OF BUILDING TECHNOLOGY STUDENTS IN TECHNICAL COLLEGES IN NIGER STATE - Kudu, Umar B. (Sokoto Educational Review, 2014)
This study was designed to determine the effects of the constructivist instructional approach on achievement and retention of Building Technology students in Technical Colleges of Niger State. A pre-test, post-test, non-equivalent control group, quasi-experimental research design was adopted. Fifty students constituted the subjects in the experimental group and 50 students constituted the subjects in the control group for the study. A total o f 100 students were involved in the study. Three research questions which include a null hypothesis, tested at 0.05 level o f significance, guided the study. The instruments were subject to validation by experts in Industrial and technology education department and Basic Technology. The reliability coefficient obtained was 0.72. Mean was used to answer the research questions; while T-test was employed to lest the hypothesis. The study revealed that students taught Building Technology using the constructivist instructional approach had a higher mean score than students taught using the conventional teaching method in cognitive achievement test, psychomotor achievement Test. In each of the cases, the high mean scores were found to be significant. Furthermore, the mean score of boys taught Building Technology using the constructivist instructional approach was higher than the mean score of girls taught using the same constructivist instructional approach in the cognitive achievement test. The researcher recommended that the National Board for Technical Education (NBTE) should consider a review of building technology curriculum for Technical Colleges with a view to incorporating the constructivist instructional approach into the teaching of Building Technology.